2015
DOI: 10.2459/jcm.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

The controversial relationship between exercise and atrial fibrillation

Abstract: Atrial fibrillation is the most common clinically significant arrhythmia observed both in the general population and in competitive athletes. The most important risk factors are all preventable by regular physical activity. However, although the benefits of moderate physical activity in controlling cardiovascular risk factors and decreasing the risk of atrial fibrillation have been extensively proved, concerns have arisen about the potential negative effects of vigorous exercise, particularly in endurance athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…The mechanism by which competitive sports predisposes athletes to AF is still a matter of intense speculation. It has been proposed that AF initiation and perpetuation occur due to an interplay of triggers, modulators, and an appropriate substrate [ 23 , 24 ]. Excessive parasympathetic and sympathetic stimulation, such as occurs in athletes, can trigger atrial ectopy and shorten action potential duration, thereby initiating and sustaining AF [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which competitive sports predisposes athletes to AF is still a matter of intense speculation. It has been proposed that AF initiation and perpetuation occur due to an interplay of triggers, modulators, and an appropriate substrate [ 23 , 24 ]. Excessive parasympathetic and sympathetic stimulation, such as occurs in athletes, can trigger atrial ectopy and shorten action potential duration, thereby initiating and sustaining AF [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive parasympathetic and sympathetic stimulation, such as occurs in athletes, can trigger atrial ectopy and shorten action potential duration, thereby initiating and sustaining AF [ 25 , 26 ]. Chronic pressure and volume overload from increased cardiac output leads to adverse anatomic and electrophysiologic remodeling, characterized by biatrial dilation, inflammation and myonecrosis, fibrosis and non-homogenous conduction [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. Conversely, moderate exercise has been shown to be protective against remodeling [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of health outcomes, a dose‐response relationship is believed to exist; additional benefits occur as the amount of physical activity increases through higher intensity, greater frequency, and/or longer duration . However, earlier studies have revealed conflicting associations between exercise intensity and atrial fibrillation (AF), a common form of cardiac rhythm disorder . Some trials reported a J‐shaped or U‐shaped correlation between physical activity level and AF with increased risk in sedentary individuals and vigorously exercising men .…”
Section: Introductionmentioning
confidence: 99%
“…5 Others have also suggested that some endurance athletes may experience extensive stiffening of the heart muscle, which might trigger atrial fribrillation at high-intensity exercise. 6 A recently emphasized concept is that of vagal atrial fibrillation, 7 which usually affects young patients with otherwise normal hearts.…”
mentioning
confidence: 99%